Stability of a mathematical model of tumour-induced angiogenesis - Li, Dan; Ma, Wanbiao; Guo, Songbai (Nonlinear Analysis: Modelling and Control, 2016)
A model consisting of three differential equations to simulate the interactions between cancer cells, the angiogenic factors and endothelial progenitor cells in tumor growth is developed. Firstly, the global existence, nonnegativity and boundedness of the solutions are discussed. Secondly, by analyzing the corresponding characteristic equations, the local stability of three boundary equilibria and the angiogenesis equilibrium of the model is discussed, respectively. We further consider global asymptotic stability of the boundary equilibria and the angiogenesis equilibrium by using the well-known Liapunov–LaSalle invariance principal. Finally, some numerical simulations are given to support the theoretical results.
Keywords: cancer; angiogenic factors; time delay; stability